Comparison between maximal respiratory pressures obtained from digital and analog manovacuometer in healthy children - Melo, Janiara Borges da Costa; Campos, Tânia Fernandes; de Freitas, Diana Amélia; Borja, Raíssa de Oliveira; do Nascimento, Rafaela Andrade; de Mendonça, Karla Morganna Pereira Pinto (Journal of Respiratory and CardioVascular Physical Therapy, 2013)
Background: The assessment of respiratory muscle strength in children is needed for clinical reasons; the instrument used to measure the strength of respiratory muscles is the manometer, which can be either analog or digital. Objectives: To compare the values obtained by analog and digital manometer in healthy children aged between 7 to 11 years old. Methods: 49 schoolchildren (25 boys) from public schools were assessed. Anthropometric measurements were collected in addition to the measurement of maximal respiratory pressures by analog and digital manometer. The paired Student’s t test was used to compare the measurements of maximal inspiratory and expiratory pressures obtained by the two instruments. The Bland-Altman analysis assessed mean differences (BIAS) and agreement between the equipment’s used. Results: No significant difference between values for maximal respiratory pressures in both devices. However, Bland-Altman analysis showed large limits of agreement between the values obtained by the two manometers. Conclusion: Data from this study demonstrate that, although no significant differences were observed between the measures obtained by the two devices in a sample of healthy children, agreement between them showed a clinically unacceptable range for measures of maximal respiratory pressure.